Production of fructose using recycle fixed-bed reactor and batch bioreactor - Rahman, N.A.; Hussain, Mohd Azlan; Jahim, J.M. (Journal of Food Agriculture & Environment, 2012)
Successful development of fructose syrup products lies in high yielding glucose-isomerizing enzymes and production reactor. This work focused on determining the optimum operating conditions for batch reactor by an overall desirability function, D, and evaluation of the performance of fructose production using three different types of reactors. Production of fructose from glucose isomerisation process using commercial immobilized glucose isomerase (IGI) was conducted in two bioreactors, a batch type of stirred tank bioreactor and in a continuous mode of column bioreactor. Initial concentration of glucose in the substrate used was 30 w/v with 6 g of dry immobilized glucose isomerase (IGI). The recycle system showed 50 enhancement in production as the operating conditions, temperature, feed flow rate and pH were conscientiously monitored and compared. The percentage isomerisation for batch reactor was much higher than the fixed-bed reactor recycling system by 81.64 at pH values of 8. The optimum operating conditions for both systems with substrate flow rates of 8 ml min -1 were at 65Â°C and pH value of 8.